PRELIMINARY STUDY OF LIPID CONTENT IN BROWN ALGAE (Sargassum binderi) FROM MANOKWARI WATERS - Stepanus, Jamius Bin (Molluca Journal of Chemistry Education (MJoCE), 2025)
Algae are marine plants that have the potential as raw material for producing biofuel (biodiesel, bioethanol and biogas) apart from being used as biomass. The high lipid content in algae can be converted into biofuel through esterification and transesterification chemical reactions. Research on the chemical composition of algae species found in West Papua remains limited. One type of algae commonly found in the waters of West Papua, especially on the northern coast of Manokwari is Sargassum binderi. Therefore, the aim of this study is to identify the types and percentages of lipid compounds contained in S. binderi. Lipid compounds were extracted using 2 different extraction methods, the maceration method and the Bligh Dyer method. The extraction process uses wet samples of S. binderi without drying, grinding or heating treatments. The type and percentage of lipids were determined via GC-MS analysis. The study results revealed six lipid compounds obtained from the maceration method: tetradecanoic acid (1.4%), 10-octadecenoic acid (4.69%), hexadecanoic acid (19.15%), 9-octadecenoic acid (Z) (5.93%), octadecanoic acid (2.71%), and 5,8,11,14-eicosatetraenoic acid (1.01%), with a total lipid compound percentage of 34.89%. Meanwhile, from the Bligh Dyer method, five lipid compounds were identified: 9-octadecenoic acid (Z) (4.33%), hexadecanoic acid (46.07%), 9,12-hexadecadienoic acid (5.23%), 11-octadecenoic acid (27.18%), and 5,8,11,14-eicosatetraenoic acid (2.81%), with a relatively high total lipid percentage of 85.62%. Hexadecanoic acid, also known as palmitic acid, was the lipid compound with the highest percentage found in both extraction methods.